2017
DOI: 10.1159/000478984
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Components in Rat Pial Arteriolar Rhythmic Diameter Changes

Abstract: This study aimed to analyze the frequency components present in spontaneous rhythmic diameter changes in rat pial arterioles. Pial microcirculation was visualized by fluorescence microscopy. Rhythmic luminal variations were evaluated via computer-assisted methods. Spectral analysis was carried out on 30-min recordings under baseline conditions and after administration of acetylcholine (Ach), papaverine (Pap), Nω-nitro-L-arginine (L-NNA) prior to Ach, indomethacin (INDO), INDO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…The diameter measures used for the analyses were obtained on 30 min tracings (acquisition frequency: 4 Hz) to obtain the resolution of the six components in the following ranges: 2.5–4.5 Hz (termed VHF, i.e., very high frequency), 0.2–2.0 Hz (HF, high frequency), 0.06–0.2 Hz (LF, low frequency),0.02–0.06 Hz (ILF, infra-low frequency), 0.0095–0.021 Hz (VLF, very low frequency), and 0.001–0.0095 Hz (ULF, ultra-low frequency; Lapi et al, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…The diameter measures used for the analyses were obtained on 30 min tracings (acquisition frequency: 4 Hz) to obtain the resolution of the six components in the following ranges: 2.5–4.5 Hz (termed VHF, i.e., very high frequency), 0.2–2.0 Hz (HF, high frequency), 0.06–0.2 Hz (LF, low frequency),0.02–0.06 Hz (ILF, infra-low frequency), 0.0095–0.021 Hz (VLF, very low frequency), and 0.001–0.0095 Hz (ULF, ultra-low frequency; Lapi et al, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the components into ranges 0.021–0.052 Hz and 0.052–0.145 Hz were correlated to the neurogenic and the intrinsic myogenic activity of vascular smooth muscle cells, respectively. Finally, the ranges 0.145–0.6 Hz and 0.6–2.0 Hz have been associated to the respiration and the heart rates, respectively (Kvandal et al, 2003 , 2006 ; Lapi et al, 2010 ). Our data indicate that oscillations in rat pial microcirculation presented quite the same ranges previously reported with the exception of the frequency component related to the heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…In rat brain, it has been reported that oscillatory patterns characterize pial blood flow (Hudetz et al, 1992 ; Ursino et al, 1998 ; Mastantuono et al, 2016a ). However, a large number of studies have shown that these oscillations in blood flow are due to the several physiological factors, regulating microvascular blood flow redistribution (Kvandal et al, 2003 , 2006 ; Lapi et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The power density spectral distribution was obtained by time averaging the time-frequency power density representation. This technique permits to evaluate non-stationary data, such as those represented by rhythmic variations in vessel diameters” (Rossi et al, 2005; Lapi et al, 2017).…”
Section: Methodsmentioning
confidence: 99%